Analisis Karakter Morfometrik Ikan Tongkol (Auxis sp) Yang Didaratkan Di Pantai Tianyar, Karangasem - Guna, Abdi Jana; Watiniasih, Ni Luh; Puspitha, Ni Luh Putu Ria (Journal of Marine and Aquatic Sciences, 2021)
Mackerel tuna is favored by many people, with high consumer need at the market, can have an impact not selectively the size of tuna catch. The problem of the size of tuna catch can be known by morphometric research. The research about morphometric mackerel tuna was done at Tianyar Beach, Karangasem, there are two types of mackerel tuna it called is bullet tuna (Auxis rochei) and frigate tuna (Auxis thazard). The difference between bullet tuna and frigate tuna is body shape, body marked, body color. Morphometric characters of bullet tuna and frigate tuna as total length (TL), standard length (PS), fork length (PC), head length (PK), head height (TK), predorsal length (PPD), prepectoral length (PPP), eye diameter (DM), operculum length (PO), maxillary length (PRA), lower jaw length (PRB), height (TB), length of the lower caudal fin (PSEB), length of the upper caudal fin (PSEA) an increase during 30 trips (February - April), the increase in morphometric size of bullet tuna and frigate tuna from Februari until April related by animal growth and evolve. Fork length frequency distribution bullet tuna has a range between 216 – 278 mm, and fork length frequency distribution of frigate tuna has a range between 230 – 299 mm. Length - weight relationship of bullet tuna is W = 0,00002  and frigate tuna is W = 0,00006 , they have the similarity about length growth faster more than weight (allometrik negative). Composition of bullet tuna is 508 and 46 individual of frigate tuna in Tianyar Beach, Karangasem during 30 trip .